Deploying containers to Azure. (Pragmatic AI Solutions, 2022)
Deploy a containerized web app to Azure There are many services out there that allow you to deploy a container to the cloud. Although a straightforward operation, it is critical to understand how to create a robust automation deployment system. This course will create a Python Flask application from scratch, will containerize it, set the automation for it and then deploy it to Azure. This course lays out the foundations for creating more powerful containerized applications beyond the simple examples. You can add a Machine Learning model into the container and the end result would be the same: a robust deployment system that can get changes quickly onto Azure with any changes to the main branch. The continuous deployment system is a game changer as a skill set, making you a far more valuable engineer. In this video you will learn: Create a Python Flask application for containerization Use a Dockerfile to create the Flask container Use GitHub Actions to automatically deploy the container after a pull request or changes to the main branch Push your container to the GitHub container registry from the GitHub repository Create the web app on the Azure portal and connect it to GitHub Actions Host the containerized Python Flask application on Azure Debugging techniques for broken containers and other common errors like incorrect ports Useful Resources GitHub repository with sample code Free Azure Certification for Students Try Azure for Free AZ-900 Azure Fundamentals reference guide Azure SAMBA file share Azure Remote Compute for VSCode.